LIBRARY ORGANIZATIONS IN THE PUNJAB PROVINCE OF PAKISTAN: AN APPRAISAL - Ahmad, Pervaiz; ur-Rehman, Shafiq (Malaysian Journal of Library and Information Science, 2017)
Library is a growing organism and librarianship is an expanding multidimensional profession. Librarianship connects people and ideas. Library organisations connect library profession and professionals. These organisations include associations, groups, and forums, whether registered or unregistered. Pakistan was born on 14 August 1947. Punjab is the largest province in Pakistan in terms of population, libraries and library schools. Punjab Library Association is the first library association in Pakistan. At present there are 11 such organisations in the Punjab province of Pakistan. This appraisal, founded upon literature review, personal communications, observation and authors’ experiences of dealing with these associations, introduces these organizations and their contribution to the cause of librarianship in the province and the country.